Reproduction Immunity Trade-Off in a Mollusk: Hemocyte Energy Metabolism Underlies Cellular and Molecular Immune Responses - Brokordt, Katherina; Defranchi, Yohana; Espósito, Ignacio; Cárcamo, Claudia; Schmitt, Paulina; Mercado, Luis; de la Fuente-Ortega, Erwin; Rivera-Ingraham, Georgina A. (Frontiers in Physiology, 2019)
Immune responses, as well as reproduction, are energy-hungry processes, particularly in broadcast spawners such as scallops. Thus, we aimed to explore the potential reproduction-immunity trade-off in Argopecten purpuratus, a species with great economic importance for Chile and Peru. Hemocytes, key immunological cells in mollusks, were the center on this study, where we addressed for the first time the relation between reproductive stage, hemocyte metabolic energetics and their capacity to support immune responses at cellular and molecular levels. Hemocyte metabolic capacity was assessed by their respiration rates, mitochondrial membrane potential and citrate synthase (CS) activity. Cellular immune parameters such as the number of circulating and tissue-infiltrating hemocytes and their ROS production capacity were considered. Molecular immune responses were examined through the transcriptional levels of two pattern recognition receptors (ApCLec and ApTLR) and two anti-microbial effectors (ferritin and big defensin). Their expressions were measured in hemocytes from immature, matured and spawned scallops under basal, and one of the following challenges: i) in in-vitro, where hemocytes were challenged ex-vivo with the β glucan zymosan, to determine the immune potentiality under standardized conditions; or ii) in-vivo challenge, using hemocytes from scallops injected with the pathogenic bacteria Vibrio splendidus. Results indicate a post-spawning decrease in the structural components of the immune system (hemocyte number/quality) and their potential capacity of performing immune functions (with reduced ATP-producing machinery and exhaustion of energy reserves). Both in-vitro and in-vivo challenges demonstrate that hemocytes from immature scallops have, in most cases, the best metabolic potential (increased CS activity) and immune performances, with for example, over 3-fold higher ROS production and tissue-infiltration capacity than those from mature and spawned scallops after the bacterial challenge. Agreeing with cellular responses, hemocytes from immature individuals induced the highest levels of immune receptors and antimicrobial effectors after the bacterial challenge, while spawned scallops presented the lowest values. Overall, results suggest a trade-off between resource allocation in reproduction and the immune responses in A. purpuratus, with hemocyte energy metabolic capacity potentially underlying cellular and molecular immune responses. Further research would be necessary to explore regulatory mechanisms such as signaling pleiotropy which may potentially underly this trade-off.